The effect of diversification on firm performance: Evidence from Listed Companies in Vietnam (International Journal of Scientific Research and Management (IJSRM), 2021)
The study was conducted to investigate the relationship between diversification on Board and firm performance. The investigation has been performed using panel data procedure for a sample of 204 Vietnamese listed companies in two different groups: Large cap and Mid cap, listed in HOSE and HNX during the period of five years from 2015 to 2019. The study uses three performance measures (including return on equity, return on asset, Tobin’s Q) as dependent variable. The independent variables for measurement of diversification on Board are the number of females and the diversification for Supervisory Board are the number of females only. Other independent variables are average age of Board member, CEO duality and the number of independent directors. The results indicated that firm performance have positive relationship with nationality diversity on Board and gender diversity on Supervisory Board. CEO duality shows a significant result of negative effect on firm performance.